PROBLEMS OF LEARNING RUSSIAN BY NATIONAL GROUP STUDENTS OF A MEDICAL UNIVERSITY - Lola Yunusovna Akramova , Gulnoza Kakhramonovna Masudova , Lyudmila Vadimovna Tomchani (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In modern Uzbekistan, there is a great interest of students in the study of the Russian language. This is due to the fact that today Russia is a country of high-quality higher education and the international labor market. After the 90s, due to the emigration of the Russian-speaking population and the loss of the status of the Russian language as a language of communication, Russian language became as foreign as English, Chinese, and other languages. Unfortunately, graduates of national schools have a very low level of language proficiency. It must be said that the Russian is studied at schools in Uzbekistan from grade 2 to grade 9; Russian classes are also provided in colleges, lyceums and universities. In total, students study the language for olmost 10 years. The paradox is that, having come to the institute, students cannot speak Russian and do not know grammar at all. A small exeption are students who grew up in Tashkent, their level of understanding and communicative skills in Russian matches to Common Underlying Proficiency (CUP)..It seems that this is due to the method of teaching the Russian language school.